Clinical course of patients with symptomatic isolated superficial vein thrombosis: the ICARO follow‐up study. (19th October 2017) - Barco, S.; Pomero, F.; Di Minno, M. N. D.; Tamborini Permunian, E.; Malato, A.; Pasca, S.; Barillari, G.; Fenoglio, L.; Siragusa, S.; Di Minno, G.; Ageno, W.; Dentali, F.
Abstract : Essentials Late sequelae of isolated superficial vein thrombosis (iSVT) have rarely been investigated. We studied 411 consecutive outpatients with acute iSVT with a median follow‐up of three years. Male sex and cancer are risk factors for future deep vein thrombosis or pulmonary embolism. Patients without cancer appear to be at a negligible risk for death. Summary: Background: Studies of long‐term thromboembolic complications and death following acute isolated superficial vein thrombosis (iSVT) of the lower extremities are scarce. Objectives: To investigate the course of iSVT in the setting of an observational multicenter study. Methods: We collected longitudinal data of 411 consecutive outpatients with acute, symptomatic, objectively diagnosed iSVT who were previously included in the cross‐sectional ICARO study. Four patients followed for < 30 days and 79 with concomitant deep vein thrombosis (DVT) or pulmonary embolism (PE) were excluded from the present analysis. The primary outcome was symptomatic DVT or PE. The safety outcomes were major bleeding and all‐cause death. Results: The median follow‐up time was 1026 days (interquartile range 610–1796). Symptomatic DVT/PE occurred in 52 (12.9%) patients, giving annualized rates of 1.3% (95% confidence interval [CI] 0.3–3.9%) on anticoagulant treatment and 4.4% (95% CI 3.2–5.8%) off anticoagulant treatment. Male sex (adjusted hazard ratio [HR] 2.03 [95% CI 1.16–3.54]) and active solid cancer (adjusted HR 3.14 [95% CI 1.11–8.93]) were associated with future DVT/PE, whereas prior DVT/PE failed to show significance, most likely because of bias resulting from prolonged anticoagulant treatment. Three major bleeding events occurred on treatment, giving an annualized rate of 1.4% (95 CI 0.3–4.0%). Death was recorded in 16 patients (annualized rate: 1.1% [95% CI 0.6–1.7%]), and was attributable to cancer ( n = 8), PE ( n = 1), cardiovascular events ( n = 3), or other causes ( n = 4). Conclusions: The long‐term risk of DVT/PE after anticoagulant discontinuation for acute iSVT is clinically relevant, especially in males and in the presence of active cancer. The risk of death appears to be negligible in patients without cancer.